2018
DOI: 10.2139/ssrn.3211416
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Regional Conflict Complexes

Abstract: Civil conflicts spill over into neighboring countries. This paper proposes a theory of the contagion of civil wars. Weak territorial control facilitates the emergence of a regional market for war inputs in the "porous frontier." The contagion effect is nonlinear and creates multiple equilibrium situations of regional complexes of civil conflicts. This helps explain the observed patterns of regional clustering of conflict and institutional quality, and raises identification issues in the measurement of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In this section, we borrow from a large literature on the spatial transmission of civil wars to instrument variation in civil wars occurrence using a historical record of conflict exposure of culturally and geographically proximate countries. 21 This literature points out to cross-border and spatial contagion as crucial determinants of the spatial distribution of civil wars, that in spite of their domestic nature tend to cluster around regions that involve more than one country (Salehyan & Gleditsch, 2006;Buhaug & Gleditsch, 2008;Silve & Verdier, 2018). 22 Similarities between neighboring countries make the formation of these regional clusters of civil wars more likely, because the conflict increases the salience of these similarities and bonds for members of the same group (Forsberg, 2014;Böhmelt & Bove, 2020).…”
Section: Endogeneity Concernsmentioning
confidence: 99%
“…In this section, we borrow from a large literature on the spatial transmission of civil wars to instrument variation in civil wars occurrence using a historical record of conflict exposure of culturally and geographically proximate countries. 21 This literature points out to cross-border and spatial contagion as crucial determinants of the spatial distribution of civil wars, that in spite of their domestic nature tend to cluster around regions that involve more than one country (Salehyan & Gleditsch, 2006;Buhaug & Gleditsch, 2008;Silve & Verdier, 2018). 22 Similarities between neighboring countries make the formation of these regional clusters of civil wars more likely, because the conflict increases the salience of these similarities and bonds for members of the same group (Forsberg, 2014;Böhmelt & Bove, 2020).…”
Section: Endogeneity Concernsmentioning
confidence: 99%
“…Tilly (1990), for example, argued that enemies of the state would be more likely to ally under larger jurisdictions to resist the concentrated coercion of a rent extractor. Furthermore, other scholars have suggested that smaller countries can better police and govern an area (Herbst 2000;Fleck and Hanssen 2013) and mitigate conflict spillovers (Silve and Verdier 2018). But this too is only one part of the picture.…”
Section: Introductionmentioning
confidence: 99%